The role of mean platelet volume (MPV) level as an independent predictor for varicocele in late adolescent - Ryuu Damara Parisudha; I Gede Suwedagatha (DiscoverSys Inc., 2020)
Background: Recent studies have reported significant associations between varicocele and platelet volume indices (PVIs). PVIs are inexpensive and widely used indicators consisting of mean platelet volume (MPV), platelet distribution width (PDW), and platelet large cell ratio (P-LCR) and are related to platelet volume and function. The possibility of PVIs as a predictor for varicocele is yet to be exposed. This study aimed to assess the role of PVIs as a predictor for varicocele in the late adolescent.Methods: This retrospective case-control study involved 89 varicocele subjects (group I) and 89 healthy controls (group II) of similar age, stature, and body mass index. The data were consecutively taken from medical records at Bhayangkara Denpasar Hospital between January 2017 and May 2019. The diagnosis of varicocele was based on the findings from both physical examination and color doppler ultrasound (CDU). PVIs indicators were analyzed among the two groups. Statistical analysis was performed using receiver operating characteristic (ROC) curve to determine optimum cut-offs, bivariate chi-square test, and multivariate analysis using binary logistic regression, with p<0.05 considered statistically significant.Results: ROC curve analysis showed optimum cut-offs of 8.05, 12.05, and 15.1 for MPV, PDW and P-LCR respectively (Youden index: 0.494, 0.326, 0.292; p < 0.001, p <0.001, p=0.001 respectively). Chi-square test showed significant associations between the PVIs indicators and varicocele (p < 0.001). Binary logistic regression analysis revealed that MPV level of â‰¥ 8.05 is an independent predictor for late adolescent varicocele (OR=6.001; 95%CI 2.547-14.139; p < 0.001).Conclusion: MPV can be used as an independent predictor for assessing varicocele in the late adolescent.